Circulating microvesicles in snakebite patients with microangiopathy. Issue 1 (22nd November 2018) - Enjeti, Anoop K.; Lincz, Lisa F.; Seldon, Michael; Isbister, Geoffrey K.
Abstract: Background: Venom‐induced consumption coagulopathy is a common consequence of snake envenoming that can lead to life‐threatening hemorrhage, and is associated with microangiopathic hemolytic anemia (MAHA), acute kidney injury and thrombocytopenia. The role of microvesicles (MV) in snakebite patients has not been previously investigated. Objective: To compare changes in subsets of circulating MV levels in snakebite patients with venom induced consumption coagulopathy and with or without microangiopathic hemolysis to those of healthy controls. Methods: This study used samples from patients recruited to the Australian Snakebite Project (ASP) with snake envenoming, including bites by brown snakes, tiger snakes, and taipans. Citrated blood from envenomed patients was collected, processed, and stored according to a national standardized protocol. Full blood count and coagulation parameters were measured as per routine clinical care and blood films were examined for evidence of hemolysis. Baseline coagulation parameters were measured on a Behring Coagulation System. Flow cytometry was performed to detect CD41a (platelet), CD62e (endothelial), and glycophorin (red cell) MV. The results were analyzed using BD software and appropriate statistical tools. Results and Conclusions: The red cell MV in snakebite patients with MAHA (n = 13) were significantly higher than those without MAHA (n = 17) while there was no significant difference in platelet MV levels between the snakebite patients with and without MAHA. Interestingly, the endothelial MV were reduced in all snakebite patient samples compared to the control samples. Measuring red cell MV at presentation could be useful as a predictive marker for MAHA in patients with snakebites.